POROČILO O PROJEKTU MESECI USTVARJALNOSTI M. J. LERMONTOVA NA UNIVERZAH V SLOVENIJI IN MEDNARODNEM ZNANSTVENEM SIMPOZIJU МIHAIL LERMONTOV V GLOBALNEM DISKURZU - Kaloh Vid, Natalia (Slavia Centralis, 2020)
The author reports on a project called Months of Creativity by Mikhail Lermontov at Universities in Slovenia, prepared by the Department of Translation Studies at the Faculty of Arts, University of Maribor in cooperation with the director of the Russian Center in Maribor, Igor Romanov.
Keywords: Russian literature; project; report; Months of Creativity by Mikhail Lermontov at Universities in Slovenia; symposium